Critical success factors of franchising firms: A study on franchisors and franchisees - Mohd Hizam Hanafiah; Mohd Faizal Abdul Ghani; Rosmah Mat Isa; Hamizah Abd Hamid (Administrative Sciences, 2023)
The franchising sector demands a high level of assurance and commitment. This is because creating entrepreneurial value is at the core of any franchising strategy. However, little is understood about what causes franchised businesses' critical success factors, particularly in developing nations like Malaysia. Hence, this study aims to identify the critical success factors in franchising business firms. The characteristics of franchisors and franchisees that can contribute to the franchise system's success in Malaysia were discovered using a focus group method by inviting franchisors and franchisees who are already running their businesses. In addition, Perbadanan Nasional Berhad (PERNAS) and the Malaysian Franchise Association (MFA), together with academicians, were also invited as a part of the focus group discussion. The findings show that three critical success factors emerged from this study, the franchisor's capability, interconnection with franchisees, and constant innovation. These three elements demonstrated that there is still room for a more significant expansion. Therefore, anyone considering joining a franchise should know it is an option. Additionally, this research helps produce a valuable model of the franchising business process that regulators, franchisors, and franchisees can use as a guide. Finally, this study also offers directions for further research.
Keywords: 350; critical success factor; focus group discussion; franchisee; franchising; franchisor